THE EXISTENCE OF PLASTIC WASTE MANAGEMENT IN THE SEA ENVIRONMENT SEEN FROM CHEMICAL SCIENCE ANGLE - Alfian Noor (Hasanuddin University, 2019)
Plastic waste from year to year in the marine environment continues to increase. This is due to its wide application and its resistance to degradation making it difficult or impossible to decompose. Plastic waste has been found in various sizes and accumulated in the body of marine life. The existence of plastic waste in the body of the marine biota even causes death. This review discusses the latest advances in research and development of methods for handling plastic waste in the marine environment.